Unplanned urban afforestation as a barrier to accessibility: A case study in Jequié – BA - Duarte Júnior, Darlan Souza; Jesus , Lanara Maria de; Santo, Fábio da Silva do Espírito (Technical and Scientific Journal Green Cities, 2024)
Urban afforestation, when well planned, brings several benefits to cities and citizens. However, when poorly planned, it can generate several economic and socio-environmental problems, such as those that hinder and/or limit people’s mobility and access to various public facilities. In this sense, the objective of this study was to evaluate the impacts of urban trees from the perspective of accessibility on the sidewalks of Avenida Lomanto Júnior, Jequié - BA, with NBR 9050/2020 being used as a parameter to evaluate the conditions of this road. Although a good part of this Avenue meets the general dimensions required, several nonconformities were observed regarding the width of the free lanes, signaling, flooring and the presence of obstacles. In several stretches, it was possible to observe the presence of trees that limit or prevent the movement of people with some type of disability or reduced mobility. Thus, considering mobility as a constitutional right, the elaboration of a project and the implementation of actions that guarantee citizenship and accessibility to all people, without any kind of distinction, are essential.